213k views
2 votes
PLEASE ANSWER ASAP will give beau ly

PLEASE ANSWER ASAP will give beau ly-example-1

2 Answers

3 votes

Answer:

h=39+16t

Explanation:

Simplifying

h(t) = 16t2 + 39t

Multiply h * t

ht = 16t2 + 39t

Reorder the terms:

ht = 39t + 16t2

Solving

ht = 39t + 16t2

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Divide each side by 't'.

h = 39 + 16t

Simplifying

h = 39 + 16t

User Patrick Simard
by
5.8k points
4 votes

Answer: 23

Hope this helps :D

User Robertovg
by
5.7k points